MUSHAF MAGHRIBI : Studi Awal Sejarah Penulisan Mushaf di Era Modern Wilayah Magrib - AZIS, FAKIH ABDUL (ojs.unsiq.ac.id, 2023)
Abstrak The Maghreb Mushaf is assigned special characteristic and properties that distinguish it from other Mushafs. Just as the letter qaf doesn't always have a two-point mark; the letter fa is a point uncertain about it; the letter nun if at the end of the word does not have a dot, and so on. Based on these problems, the author would like to show how the history of the development of the Maghreb Mushaf of Al-Quran is. Then what is the basis in the guidelines for writing the Maghreb Mushaf. This research uses a descriptive-analytical method of investigation into the Maghreb Mushaf. By trying to explain the historical roots and copyists of the Mushaf from the advent of Islam to the present day. And how the writing of Maghreb Mushaf is growing rapidly in the Moroccan Kingdom. The results of this study concluded that the person who first brought the Mushaf al-Quran to the Maghreb region was Abdurrahman ad-Dakhil. The Mushaf he brought was a delivery from Sayyidina Uthman to the people of Sham. While the guidelines for writing the Mushaf al-Quran of Maghrib use the rules of Imam Al-Dany in its diacritical marks. Keywords: Mushaf, Maghreb, History, Diacritic, Al Dany